ASSESSMENT OF LEFT ATRIAL FUNCTION IN PATIENTS WITHMITRAL VALVE DISEASES - ALPHONSA MATHEW; RANJAN SHETTY; KRISHNANANDA N; NAVIN PATIL; N, Karthik rao; JYOTHI SAMANTH; BALAJI O; DIPANJAN B; RAHUL KOTIAN (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective:To observe and assess left atrial (LA) function by observing the differences in conventional Doppler echo parameters of left ventricular inflow, Left atrial appendage, among patients with mitral valve disease. Methods: Forty three mitral valve disease subjects appearing consecutively for echocardiogram (ECHO) test at the cardiology department in a tertiary care hospital were recruited into the study as per the pre-set inclusion and exclusion criteria. The data from the ECHO was pooled using Microsoft excel and analyzed using SPSS software by application of appropriate statistical tests. Results:Of the 43 objects, 39 had MS, 3 had MR and 2 of them were found to have both MS and MR. The major presenting symptom as observed in 33 subjects, was dyspnea. LA maximum volume was found to be 91Â±59 ml and minimum was 66Â±51 ml. Left atrial expansion index was 128Â±91. Left atrial active emptying fraction was 29Â±13 and passive emptying fraction was 31Â±15. No significant change in LA global strain among groups with MR and without MR was observed. Further, no significant difference was observed in left atrial indices like left atrial emptying fraction, left atrial passive emptying fraction, atrial fraction, Left atrial expansion index amongÂ Â groups having MR and no MR. Conclusion:LA contractile, reservoir and conduit function was significantly reduced in mitral valve diseases due to increased hemodynamic load. No significant difference was noted in global LA strain irrespective of MS or MR. Key Words: Valvular disease; Left atria; Strain; Contractile function